Community Perception of Tuberculosis Management Program in Suburban Surabaya: A Qualitative Study - Mundakir, .; Asri, .; Winata, Septian G.; Wiliyanarti, Pipit F.; Priyanti, Ratna P. (KnE Life Sciences, 2021)
Tuberculosis (TB) is still one of the main infectious diseases in Indonesia. The national program, Directly Observed Treatment short course (DOTS), that began in 2014 is unable to deal with TB cases comprehensively. The community has an important role in TB management because they directly intersect with patients and public health. The aim of this study is to explore the condition of the TB management program. A descriptive qualitative study was conducted in three sub-districts with high cases of TB. A semi-structured interview was conducted with 25 participants drawn from the suburban TB task force, community health volunteer groups, Community health Nurses, and subdistrict officers. Results reveal four themes which affect the implementation of TB management programmes: volunteer shortage, do for humanitarian intention, the myth and stigma, providing social and economic support. In conclusion, communitybased TB management needs to be improve in the availability of budget, staff, training and resources while maintaining the ongoing work of the TB task force team. Keywords: Community-based management, Community Health Volunteer, Descriptive Qualitative, Humanitarian Intention, Social support, TB.